What Factors Hindered the Access to Essential Anticancer Medicine in Public Hospitals for the Local Population in Hubei Province, China - Chen, Chaoyi; Feng, Zhanchun; Ding, Yufeng; Yan, Ziqi; Wang, Jia; Wang, Ruoxi; Feng, Da (Frontiers in Pharmacology, 2021)
Background Cancer poses a serious threat to one’s health, which caused significant economic burden on the family and society. Poor availability and affordability resulted in some essential medicines failing to meet the basic health needs of this group of patients. The objective of this study was to evaluate the availability, prices and affordability of 32 anticancer essential medicines in Hubei Province, China. Methods Data on the availability and price related information of 32 essential anticancer medicines in the capital and five other cities of Hubei Province were collected. A total of 28 hospitals were sampled, which included 13 tertiary hospitals and 15 secondary hospitals. We used the standard methods developed by the World Health Organization (WHO) and Health Action International (HAI) to compare the differences in drug price, availability and affordability between secondary hospitals and tertiary hospitals. Results Overall, the availability of medicine was higher in tertiary hospitals. The average availability of originator brand (OBs) was 13.70% (tertiary hospitals) VS 6.67% (secondary hospitals), and lowest-priced generic (LPGs) was 62.83% (tertiary hospitals) VS 42.92% (secondary hospitals). The MPR value of most sampled medicines in secondary hospitals were less than 1. In contrast, the MPR of Cytarabine (17.15), Oxaliplatin (12.73) were significantly higher than the international reference price. The top three OBs’ total expenses for 30-day treatment were Irinotecan, Oxaliplatin, Bicalutamide. Further, their affordability was relative low, as the costs for one course using these medicines were much higher than 20% of the minimum family monthly income. Conclusion Though the “Zero Mark-Up” and “Centralized procurement policy of anti-tumor drugs” policies have been implemented in China, the availability issue yet to be addressed. High price and low affordability were the major barriers to the access of essential anticancer medicines. Measures should be taken to provide sufficient, available and affordable medicines to patients in need.